Korupsi dalam Sorotan Etika Kristen dan Implikasinya Bagi Pendidikan Anti Korupsi - Sostenis Nggebu (Didache: Journal of Christian Education, 2021)
This article addresses the problem of corruption in Christian ethics based on the reference of God's word. Christians involved in corruption show that carrying out governmental duties is outside the control of God's word. To examine this topic more deeply, the author uses descriptive methods and literature studies. The results and conclusions of this study show that the corruptors prioritize the works of the flesh, worship material things, give in to worldly temptations, violate Christian morality, and do not glorify God in their lives. Those corrupt Christian bureaucrats who are dominated by greed and greed are not the characters expected by God, and by doing so, they lose the opportunity to be witnesses of Christ in the world. Corruption is bad behavior, so there is an opportunity for the church to pay attention to anti-corruption education for the congregation so that those who sit in government can carry out their duties and responsibilities by the demands of the Christian faith.